2017
DOI: 10.29074/ascls.30.1.15
|View full text |Cite
|
Sign up to set email alerts
|

The Professional Socialization of Early Career Medical Laboratory Scientists

Abstract: The medical laboratory science profession has faced more than twenty-years of a workforce shortage. One component that plays a role in the workforce shortage is the attrition of early career medical laboratory scientists shortly after graduation from an accredited medical laboratory science educational program. This study seeks to identify factors that contribute to the professional socialization of early career clinical laboratory scientists. In this study early career medical laboratory scientists' express h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…This highlights the importance of measuring the impact of educational interventions on broader outcomes, such as quality of client care. It is particularly essential to promote professional socialization and to develop the professional identity of the newly graduated MLS students during their transition from the classroom into the medical laboratory workforce [ 23 ]. Other studies have shown that clinical rotation sites, work environment, and employment benefits influence MLS graduates’ satisfaction levels and attitudes toward their MLS clinical training, recruitment, and even future job selection [ 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the importance of measuring the impact of educational interventions on broader outcomes, such as quality of client care. It is particularly essential to promote professional socialization and to develop the professional identity of the newly graduated MLS students during their transition from the classroom into the medical laboratory workforce [ 23 ]. Other studies have shown that clinical rotation sites, work environment, and employment benefits influence MLS graduates’ satisfaction levels and attitudes toward their MLS clinical training, recruitment, and even future job selection [ 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical practicum provides students with an opportunity to learn basic skills and experience, as it bridges the gap between theory and practice in classrooms and the clinical environment, respectively [15]. The expansion of scientific and technological innovations in clinical laboratories induces profound changes in laboratory services, ultimately exerting a significant impact on the expected roles of new graduates.…”
Section: Discussionmentioning
confidence: 99%
“…However, these teachers were overloaded by their dual role, as they were serving as clinical educators and health care providers, with some managerial and administrative tasks at the same time. Indeed, assessing the teaching and educational practices in any health care system is crucial to maintain the quality of clinical education in any clinical professions [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we distributed the competency questionnaires to gather the opinions of experts in Japan by using the Delphi method. Our expertise focused on novice MLSs, which were defined as those with fewer than 3 years of post-graduation employment experience [26]. In other medical professions, such as nursing, a competent nurse is regarded as one who has been on the job for 2-3 years [27].…”
Section: Methodsmentioning
confidence: 99%